The pros and cons of the invasive freshwater apex predator, European catfish Silurus glanis, and powerful angling technique for its population control. (1st July 2019) - Vejřík, Lukáš; Vejříková, Ivana; Kočvara, Luboš; Blabolil, Petr; Peterka, Jiří; Sajdlová, Zuzana; Jůza, Tomáš; Šmejkal, Marek; Kolařík, Tomáš; Bartoň, Daniel; Kubečka, Jan; Čech, Martin
Abstract: Catfish have spread across Europe and several countries out of this region within the last decades. Basic knowledge of this apex predator has revealed concerns of invasive behaviour and questions regarding its utilization as a biomanipulation species. However, a method enabling its regulation to a required level has not yet been developed. We simulated the impact of angling on the catfish population by method of hook-lines in two post-mining lakes with a monitored population consisting of tagged individuals and in two reservoirs as reference sites. Further, the efficiency of hook-lines as a reducing device was examined and the economic aspects were determined. Catfish population in localities where the species is unwanted or invasive may be efficiently reduced to a harmless level by hook-lines and angling (depending on the approach of anglers). The most efficient time of the year seems to be spring to early summer with catch efficiency of 5.4 individuals per 10 baits in one day. The catch efficiency markedly decreased during the second part of the year and did not exceed 2.8 individuals per 10 baits in one day. Mean size of catfish had negative impact whereas catfish biomass had positive impact on the catch efficiency. Trophic status and number of catfish in the locality had no impact on the catch efficiency. According to model, 11–18 bait-days per 1 ha per season is efficient to decrease catfish population to 10% of the original size. Both angling and hook-lines are very simple, they are financially and time bearable mechanisms of catfish regulation in any condition. However, catfish play an important role as a biomanipulative species in many localities. In this case where catfish is beneficial, angling presents a real threat of population collapse and loss of the biomanipulative effect. Graphical abstract: Image 1 Highlights: Hook-lines and angling are methods that efficiently reduce a catfish population. Relatively low effort resulted in a reduction of the catfish population. Angling presents a real threat of population collapse, where catfish is beneficial. Where catfish species is unwanted, both methods may be efficiently provided.